2006
DOI: 10.1016/j.idc.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis

Abstract: In the past 2 decades, Cryptococcus has emerged in its clinical significance and as a model yeast for understanding molecular pathogenesis. C neoformans and C gattii are currently considered major primary and secondary pathogens in a wide array of hosts that are known to be immunocompromised or apparently immunocompetent. A recent outbreak of C gattii infections further underscores the clinical importance of the yeast through its epidemiology and pathogenicity features. With an enlarging immunosuppressed popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
337
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(355 citation statements)
references
References 205 publications
5
337
0
13
Order By: Relevance
“…1,10 A systematic review of the manuscripts published after 1 January 1998 was performed in order to confirm the established utility of Cryptococcus Ag testing in disseminated cryptococcosis, Cryptococcus meningitis and pulmonary cryptococcosis. 29 Seven studies, mostly retrospective (6/7) and single-centre (4/7), were included for the analysis of diagnostic performance. [30][31][32][33][34][35][36] The sensitivity of serum Ag was higher than that of blood cultures (87% vs 42%), and it was higher in AIDS patients (in whom disseminated disease with fungemia is most frequently observed) when compared with non-HIV immunocompromised subjects (95% vs 77%).…”
Section: Cryptococcus Agmentioning
confidence: 99%
“…1,10 A systematic review of the manuscripts published after 1 January 1998 was performed in order to confirm the established utility of Cryptococcus Ag testing in disseminated cryptococcosis, Cryptococcus meningitis and pulmonary cryptococcosis. 29 Seven studies, mostly retrospective (6/7) and single-centre (4/7), were included for the analysis of diagnostic performance. [30][31][32][33][34][35][36] The sensitivity of serum Ag was higher than that of blood cultures (87% vs 42%), and it was higher in AIDS patients (in whom disseminated disease with fungemia is most frequently observed) when compared with non-HIV immunocompromised subjects (95% vs 77%).…”
Section: Cryptococcus Agmentioning
confidence: 99%
“…Cryptococcus neoformans is subdivided in three varieties and five serotypes: Cryptococcus grubii (serotype A), Cryptococcus neoformans (serotypes D and AD) and Cryptococcus gattii (serotypes B and C) 1 . C. gattii (serotypes B and C) is mainly found in tropical and subtropical climates, predominately affecting immunocompetent individuals, and is isolated from a variety of environmental sources 1 .…”
Section: Introductionmentioning
confidence: 99%
“…C. gattii (serotypes B and C) is mainly found in tropical and subtropical climates, predominately affecting immunocompetent individuals, and is isolated from a variety of environmental sources 1 . Meningoencephalitis caused by C. gattii in apparently immunocompetent HIV-seronegative individuals occurs throughout tropical latitudes, and particularly in parts of South-East Asia and Australia 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus neoformans and Cryptococcus gatti [50] represent the main pathogenic species in the genus Cryptococcus [51]. While cryptococcosis has been most commonly encountered in the HIV infected population [52], a multicenter study reporting 306 cases of cryptococcosis in non-HIV-infected patients found 0.7% of total cases occurred in HSCT recipients, 18% in SOT recipients, 9% in patients with hematologic malignancies, and 9% in patients with other malignancies [53].…”
Section: Cryptococcusmentioning
confidence: 99%